Computational study of a single-phase flow in packed beds of spheres - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
Packed-bed reactors are widely used in petrochemical, fine chemical, and pharmaceutical industries. Detailed knowledge of interstitial flow in the void space of such packed-bed reactors is essential for understanding the heat and mass transfer characteristics. In this paper, fluid flow through the array of spheres was studied using the unit-cell approach, in which different periodically repeating arrangements of particles such as simple cubical, 1-D rhombohedral, 3-D rhombohedral, and face-centered cubical geometries were considered. Single-phase flow through these geometries was simulated using computational fluid dynamics (CFD). The model was first validated by comparing predicted results with published experimental and computational results. The validated model was further used to study the effect of particle arrangement/orientation on velocity distribution and heat transfer characteristics. The simulated results were also used to understand and to quantify, relative contributions of surface drag and form drag in overall resistance to the flow through packed-bed reactors. The model and the results presented here would be useful in elucidating the role of microscopic flow structure on mixing and other transport processes occurring in packed-bed reactors. (C) 2005 American Institute of Chemical Engineers.
Keywords: CFD; drag; heat transfer; packed bed; packing arrangement

Dynamics of drop impact on solid surface: experiments and VOF simulations - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
The process of spreading/recoiling of a liquid drop after collision with a flat solid surface was experimentally, and computationally studied to identify the key issues in spreading of a liquid drop oil a solid surface. The long-term objective of this study is to gain an insight in the phenomenon of wetting of solid particles in the trickle-bed reactors. Interaction of a falling liquid drop with a solid surface (impact, spreading, recoiling, and bouncing) was studied using a high-speed digital camera. Experimental data oil dynamics of a drop impact on flat surfaces (glass and Teflon) are reported over a range of Reynolds numbers (550-2500) and Weber numbers (2-20). A computational fluid dynamics (CFD) model, based on the volume of fluid (VOF) approach, was used to simulate drop dynamics on the flat sufaces. The experimental results were compared with the CFD simulations. Simulations showed reasonably good agreement with the experimental data. A VOF-based computational model was able to capture key features of the interaction of a liquid drop with solid surfaces. The CFD simulations provide information about finer details of drop interaction with the solid surface. Information about gas-liquid and liquid-solid drag obtained from VOF simulations would be useful for CFD modeling of trickle-bed reactors. (C) 2004 American Institute of Chemical Engineers.
Keywords: CFD; drop impact; recoiling; spreading; trickle bed; VOF